Removal and Retirement of Judges in Missouri: A Field Study - William Braithwaite (Washington University Law Quarterly, 1968)
The American Bar Association decided at its 1965 annual meeting to initiate a general study of judicial removal, discipline, and retirement. The American Bar Foundation, independent research affiliate of the ABA, agreed to do the research, which began in April 1966. As subsequently developed, the plan for research called for field studies in Missouri, Illinois, New York, New Jersey, and California. The purpose of the field studies was to learn how these jurisdictions deal in actual practice with the problems of judicial misconduct, disability, and incompetence. This Article is based upon the research in Missouri, the first field study to be completed.
Keywords: Judges